Implementation Of Yogyakarta City Government Circular Number 660/6123 / SE / 2022: Zero Inorganic Waste Movement in Terms Of The Health And Economic Sector - Wijaya, Norra Hendarni; Apriyani, Henny (IJBLE Scientific Publications Community Inc., 2024)
The Yogyakarta city government continues to intensify the socialization of the zero inorganic waste movement which will be implemented from January 2023. The move was made to reduce the volume of waste thrown into landfills as they are in near-full condition. To carry out its responsibilities and as a form of concern for the environment, the Yogyakarta city government and the Yogyakarta city community are obliged to carry out the zero inorganic waste movement. This research is a descriptive qualitative conducted in the environment of the Department of Environment and community surrounding totaling 8 people. Data collection through observation and in-depth interviews, while data analysis using data reduction is processed and then narrated and drawn conclusions. The results showed that most people have begun to understand and conduct waste sorting as a result of the socialization carried out by the government will be zero inorganic waste. It's just that there are some houses that sometimes still don't want to sort out their own garbage before being thrown away. This is seen from the results of interviews that have been conducted in the environment around the city of Yogyakarta. The biased conclusion is that most of the people in the city of Yogyakarta have begun to sort garbage as seen from the observations that have been made. The environment looks clean and tidy in most areas.